Outcomes of COVID-19 in kidney transplant recipients in the vaccination Era: A national multicenter cohort from Thailand - Suwasin Udomkarnjananun; Stephen J. Kerr; Athiphat Banjongjit; Korntip Phonphok; Nuttasith Larpparisuth; Attapong Vongwiwatana; Kajohnsak Noppakun; Adisorn Lumpaopong; Thanom Supaporn; Cholatip Pongskul; Yingyos Avihingsanon; Natavudh Townamchai (Heliyon, 2023)
Introduction: The mortality rate of coronavirus disease 2019 (COVID-19) in kidney transplant recipients (KTR) has significantly decreased with the implementation of vaccination programs. However, the real-world information on the impact of vaccinations, particularly in resource limited settings in Asia, is still limited. Methods: The Thai Transplant Society conducted a prospective multicenter cohort registry, including KTR diagnosed with COVID-19. Cox proportional hazards regression was used to examine factors associated with poor COVID-19 outcomes and complications, including death, COVID-19 pneumonia, and superimposed bacterial infection. Results: A total of 413 patients from 17 transplant centers who developed COVID-19 were analyzed. The COVID-19 mortality rate was 5.6 % and the incidence of pneumonia was 18.8 %. With each 10-year increase in age, the risk of death, pneumonia, and bacterial infection increased by 61 %, 32 %, and 43 %, respectively. A total of 11.4 % of KTR received one dose of COVID vaccination (incomplete vaccination), 25.7 % received two doses (complete primary vaccination), 42.6 % received three doses (first booster dose), and 10.4 % received four doses of vaccination (second booster dose). Even a single dose of vaccination significantly decreased the risk of death, pneumonia, and superimposed bacterial infection among KTR compared to those who remained unvaccinated. Completing the primary vaccination (2-dose) reduced the risk of death by 89 %, pneumonia by 88 %, and bacterial infection by 83 % compared to unvaccinated KTR. Receiving a booster dose (third or fourth dose) further reduced the risk of death by 94 %, pneumonia by 95 %, and bacterial infection by 96 % compared to unvaccinated individuals. Conclusions: This Asian cohort demonstrated that the mortality and complications of COVID-19 significantly decreased in KTR after the national immunization. Our study suggests that any type of COVID-19 vaccine can be beneficial in preventing adverse outcomes. Administering booster vaccinations is strongly recommended.